Noise 2018
DOI: 10.1136/oemed-2018-iseeabstracts.54
|View full text |Cite
|
Sign up to set email alerts
|

OP XI – 6 Evaluation and prediction of indoor and outdoor noise differences in residential dwellings using statistical model

Abstract: Background/aimMost epidemiological studies investigating the association between noise exposure and health use modelled outdoor noise estimates as exposure proxy. This study aims to explore the relationship between indoor and outdoor noise at residential dwellings in London and evaluates potential parameters of dwelling ad sound insulation characteristics to predict the indoor exposure.MethodsMeasurements were done at 49 homes mostly in winter and spring seasons when windows are closed. Continuous noise measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Third, estimating noise exposure based on residential addresses and outdoor measurements, which assumes indoor noise levels, may have introduced bias. Although previous studies have shown a good correlation between indoor and outdoor noise levels [33,34], limitations remain owing to the estimation of noise using Geographic Information System (GIS) spatial analysis for areas without noise information. Because noise measurement points are designated to represent noise levels considering factors such as population and area, our kriging method implemented for areas with a lower priority for measurement may not accurately re ect noise information.…”
Section: Discussionmentioning
confidence: 99%
“…Third, estimating noise exposure based on residential addresses and outdoor measurements, which assumes indoor noise levels, may have introduced bias. Although previous studies have shown a good correlation between indoor and outdoor noise levels [33,34], limitations remain owing to the estimation of noise using Geographic Information System (GIS) spatial analysis for areas without noise information. Because noise measurement points are designated to represent noise levels considering factors such as population and area, our kriging method implemented for areas with a lower priority for measurement may not accurately re ect noise information.…”
Section: Discussionmentioning
confidence: 99%
“…The weak correlation between the indoor and outdoor noise observed in this study agrees with the findings of other studies that also found weak associations between indoor and outdoor noise. [29][30][31] These studies, however, were conducted in occupied suites and indoor noise was likely affected by noise generated from occupants' activities. In the current study, measurements were conducted in unoccupied suites and noise from the HVAC systems is identified as the main reason for the weak correlation.…”
Section: Relationship Between Indoor and Outdoor Noisementioning
confidence: 99%
“…Graham et al 28 and Pirrera et al 29 measured nighttime noise levels to estimate the indoor exposure levels due to traffic noise. Naim et al 30 measured indoor noise levels due to aircraft, road and railway traffic for 3 days per building. They found a weak correlation between indoor and outdoor noise which they indicate is mainly due to the lack of suitable locations to place the indoor and outdoor noise monitoring stations in occupied buildings.…”
Section: Introductionmentioning
confidence: 99%